Population Numbers and Physiological Response of an Invasive and Native Thrip Species Following Repeated Exposure to Imidacloprid - Zhang, Xiaoming; Li, Ru; Hu, Changxiong; Chen, Guohua; Xu, Haiyun; Chen, Zhixing; Li, Zhengyue (Frontiers in Physiology, 2020)
Frankliniella occidentalis and F. intonsa are devastating pest insects of Rosa rugosa, Chrysanthemum morifolium and Phaseolus vulgaris, which are important economical horticultural plants in China. Meanwhile, R. rugosa and C. morifolium are important cash plants in Kunming, South China. We focus on the population performance of this two thrips species on these three host plants with or without repeated exposure to imidacloprid in Kunming. In the field, the population numbers of F. occidentalis developed faster and was larger on these three sampled host plants, especially under imidacloprid exposure, compared with F. intonsa. The activity of the detoxifying enzymes (CarE, AchE, MFO) and the antioxidant enzymes (CAT and POD) in both thrip species were significantly enhanced under imidacloprid exposure, whereas the activities of SOD in both thrips were significantly decreased on these three host plants, compared with the control. Overall, enzyme activity of F. occidentalis showed an increase than that observed in F. intonsa in most cases, which could be exploited in further studying thrips resistance management.